If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -5 + 3x = -5 Reorder the terms: -5 + 8x + 3x = -5 Combine like terms: 8x + 3x = 11x -5 + 11x = -5 Add '5' to each side of the equation. -5 + 5 + 11x = -5 + 5 Combine like terms: -5 + 5 = 0 0 + 11x = -5 + 5 11x = -5 + 5 Combine like terms: -5 + 5 = 0 11x = 0 Solving 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '11'. x = 0 Simplifying x = 0
| 1/2(x-40)=45 | | (15x+30)+10=180 | | (c^2-36)= | | (7y+5)=14 | | 4(x-10)=2x+10 | | 6x-41=39+x | | 616.3/5 | | 10x+4+x=4+11-1 | | 5x+20=5(x+3) | | 3-x=2+x | | 5x+20=5(4x+3) | | 4+(30*x)=195 | | 2(x-3)=-5-2(x-3) | | 3y+4x=120 | | 4xsquared+3600=0 | | 2+0=y | | 50.7=5/9(f-32) | | .2x+.3=-.7x-2.1 | | 1/12j=1/4j | | 8/3×(−212) | | 4x=3x+2.25 | | 2x^2-10=42 | | c+a=2200 | | f(x)=(1/2)6-3 | | 2y+7=112 | | 25n^2+50n+16=0 | | 6x+11=7x-8 | | f(6)=(1/2)x-3 | | 3/5g−13=−10/3 | | 8q+-9q=4 | | x*0.2=0.17 | | (13x-37)=41 |